Relationships as regulators of discourse interaction in Spanish - Romera, Magdalena (Círculo de Lingüística Aplicada a la Comunicación, 2019)
In this paper we argue that in analyses of discourse interaction the relationship between participants must be considered as a parameter that conditions their linguistic behavior. A relationship is the result of the experiences shared by partners which create a “cultural code” between them. Each relationship brings a set of circumstances into play that regulates how members behave and how they interpret each other’s words and actions. Our proposal stems from observing how Spanish speakers who hold different types of relationships handle opposing points of view in conversation. Our results show that the expression and interpretation of dissent is linked to the interlocutors’ need to maintain the relationship in good terms. In order to protect relationships, the basic principle guiding interaction is to reach consensus. Additionally, the type and strength of the relationship condition the impact of expressions. Strong disagreement is allowed in strong relationships, as the risk for its affecting the relationship is low. Conversely, weak disagreement is preferred in weak relationships, since opposing views may result in higher impact.